Perspektif sebagai Pengembangan Literasi Media Digital Mahasiswa - Adithiyo Saputro; Noor Afy Shovmayanti (ANALOGI Jurnal Ilmu Sosial dan Humaniora, 2024)
Digital media literacy is an understanding of understanding and interpreting information spread across various media, including social media. Behavioural transformation in digital media literacy is the key to using social media wisely amidst open information. Digital media literacy in the digital space is the main key in various aspects of life, including activities such as banking transactions, learning processes, searching for information, job opportunities, education, exploring modern or new lifestyles, utilizing facilities, checking weather conditions, looking for a life partner, as well as establishing social relations with UTY students. The development of media technology is directly proportional to the increase in the number of internet media users in Indonesia, which is currently recorded at 213 million at the beginning of 2023, equivalent to 77% of the total population of Indonesia with internet penetration and contribution of around 99.16 at the age of 13-18 years, and age 19-34 years old, there are around 98.64%. The results of the research obtained are that UTY students' understanding of digital literacy related to the Perspektif account has a positive impact by creating unique and inspiring narratives, playing an active role in creating content, connecting emotionally to stories on the Perspektif Instagram account, and forming social and cultural bonds. The unique and inspiring stories in UTY Perspektif make a significant contribution to students' understanding and development of digital literacy through various identified dimensions.